Taxonomy and distribution of the salamander genus Bolitoglossa Duméril, Bibron & Duméril, 1854 (Amphibia, Caudata, Plethodontidae) in Brazilian Amazonia - Brcko, Isabela Carvalho; Hoogmoed, Marinus Steven; Neckel-Oliveira, Selvino (Zootaxa, 2013)
For nearly 40 years Bolitoglossa paraensis has been synonymized with Bolitoglossa altamazonica. This fact has been mainly related to taxonomic ambiguities arising from the morphological similarities between these species and the scarcity of material deposited in collections. However, during the past 30 years new material of Bolitoglossa has been collected in many places throughout the Brazilian Amazonia, including the type locality of B. paraensis, Santa Isabel do Pará. In this article we designate the neotype of B. paraensis based on new material from the type locality, correct misinterpretations about this name. We determined how many species of the genus Bolitoglossa occur in Brazilian Amazonia, described three new species, B. caldwellae sp. nov., B. madeira sp. nov., and B. tapajonica sp. nov., provide a key for identifying Brazil-ian salamanders. Were analyzed two hundred and seventy eight specimens of Bolitoglossa from the Brazilian states of Acre, Amapá, Amazonas, Pará, and Rondônia; morphological data of B. altamazonica from Colombia were used for com-parison purposes. We confirm the presence of B. altamazonica in extreme western Brazil, and expand the number of spe-cies occurring in Brazilian Amazonia to five.